Psychological Aspects of Social Axioms - Leung, Kwok (2017)
"This work provides ways to characterize cultures, and gives researchers a set of lenses for looking at cultures. When researchers know what people value and how they use the axioms, they can predict what people will do in their cultural niche - how they are likely to interact with each other, how they are likely to relate to outsiders, how they are going to react to their jobs, what emotions they are likely to feel in different circumstances, and how are they going to deal with conflict."